Binding of cml-modified as well as heat-glycated β-lactoglobulin to receptors for ages is determined by charge and hydrophobicity - Zenker, Hannah E.; Teodorowicz, Malgorzata; Ewaz, Arifa; Joost van Neerven, R. J.; Savelkoul, Huub F.J.; De Jong, Nicolette W.; Wichers, Harry J.; Hettinga, Kasper A. (International Journal of Molecular Sciences, 2020)
Intake of dietary advanced glycation end products (AGEs) is associated with inflammation-related health problems. Nε-carboxymethyl lysine (CML) is one of the best characterised AGEs in processed food. AGEs have been described as ligands for receptors present on antigen presenting cells. However, changes in protein secondary and tertiary structure also induce binding to AGE receptors. We aimed to discriminate the role of different protein modifications in binding to AGE receptors. Therefore, β-lactoglobulin was chemically modified with glyoxylic acid to produce CML and compared to β-lactoglobulin glycated with lactose. Secondary structure was monitored with circular dichroism, while hydrophobicity and formation of β-sheet structures was measured with ANS-assay and ThT-assay, respectively. Aggregation was monitored using native-PAGE. Binding to sRAGE, CD36, and galectin-3 was measured using inhibition ELISA. Even though no changes in secondary structure were observed in all tested samples, binding to AGE receptors increased with CML concentration of CML-modified β-lactoglobulin. The negative charge of CML was a crucial determinant for the binding of protein bound CML, while binding of glycated BLG was determined by increasing hydrophobicity. This shows that sRAGE, galectin-3, and CD36 bind to protein bound CML and points out the role of negatively charged AGEs in binding to AGE receptors.
Created from Fastlane, Scopus look-up
Keywords: CD36; Charge; Galectin-3; Glycation; Milk protein; Nε-carboxymethyl lysine; SRAGE